2016
DOI: 10.1002/pad.1784
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization as a Post‐Conflict Stabilization Tool: The Case of Sierra Leone

Abstract: Summary Sierra Leone's experience with decentralization as a post‐conflict stabilization tool highlights both the value of making and keeping a promise to empower citizens through local government and the importance of fully implementing that promise over a longer time horizon. The emergence of the country from civil conflict into peace and stability is one of the greatest success stories of post‐conflict stabilization. Although the nation has enjoyed over a decade of peace (and peaceful transitions from party… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The first strand discussed the general impacts of decentralization in various country settings. While some suggested that decentralization could be an effective tool for enhancing local accountability and creating more responsive governance institutions (Crook, 2003; Edwards & Yilmaz, 2016; Yan and Xin, 2017), some others showed that decentralization had not enhanced subnational government responsiveness as expected, especially in weak states (Lewis, 2014; Wunsch, 2013; Xin et al, 2022). A mixed effect of decentralization on governance has also been evinced in empirical studies more broadly (Faguet, 2014; Treisman, 2007).…”
Section: Central‐local Relation and The Paradox Of Epidemic Control I...mentioning
confidence: 99%
See 2 more Smart Citations
“…The first strand discussed the general impacts of decentralization in various country settings. While some suggested that decentralization could be an effective tool for enhancing local accountability and creating more responsive governance institutions (Crook, 2003; Edwards & Yilmaz, 2016; Yan and Xin, 2017), some others showed that decentralization had not enhanced subnational government responsiveness as expected, especially in weak states (Lewis, 2014; Wunsch, 2013; Xin et al, 2022). A mixed effect of decentralization on governance has also been evinced in empirical studies more broadly (Faguet, 2014; Treisman, 2007).…”
Section: Central‐local Relation and The Paradox Of Epidemic Control I...mentioning
confidence: 99%
“…Second, our application and extension of the decentralized governance framework speak to the debate on the effects of decentralization on government performance (Crook, 2003; Edwards & Yilmaz, 2016; Erkoreka & Hernando‐Perez, 2022; Qian & Mok, 2016; Wunsch, 2013) by offering three novel observations on the Chinese local government responses to COVID‐19. It unveiled an inherent incentive‐information asymmetry between the central and local authorities that underlies the government's responses to the outbreak in its early stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decentralization is one of the stabilization strategies. Studies showed that decentralization can prevent and reduce conflicts, especially those caused by ethnic problems (Edwards & Yilmaz, 2016). However, in the context of Papua, the decentralization implemented resulted in a different outcome because the decentralization failed to accommodate the interests of the Papuan people, both in terms of welfare and conflict resolution with separatist groups in Papua (Lele, 2021).…”
Section: Is the Expansion Of Territories The Amalgamation Of Conflict?mentioning
confidence: 99%
“…By summarizing the lessons learned from Nepal's transition to a federal system, the paper contributes to multidisciplinary literature on the relationship between conflict and decentralization; capacity and decentralization; sequencing of decentralization reforms and determinants of success in public service reforms. In terms of conflict and decentralization, despite the disagreement in the literature about the sustainability of peace and effectiveness of decentralization as a post-conflict stabilization tool, the consensus seems to be that a lot depends on the country context (Dickovick, 2014;Edwards & Yilmaz, 2016). This paper employs qualitative methods for better understanding of the country context in the implementation of federalism and asses the durability of new federal institutions to safeguard the peace dividends of the new system.…”
Section: Introductionmentioning
confidence: 99%